Upaya Hukum Terhadap Kelalaian Jasa Transportasi Hewan Ternak - Fahlani, Soffyan Angga; Mustika, Cindyva Thalia (Banua Law Review, 2023)
Moving on from partner problems, namely the minimal level of participation of Padang village women in village governance, both in terms of nominating village heads and/or becoming village heads, BPD heads, or other strategic positions in the village; the lack of participation and the role of Padang village women in preparing village development programs and drafting village regulations and the role of Padang village women in meetings in the village are still passive / less active 'listeners' in conveying opinions and suggestions. The output target of this community service activity is to increase the insight and knowledge of village cadres about the importance of women's participation in village government. The implementation stages carried out to overcome the above problems consist of three stages, namely: (1) preparation, (2) implementation, and (3) evaluation. In the preparation stage, administrative preparations, location and tools required during the implementation of the activity will be carried out. Then, the next step is the implementation stage. At this stage an increase in knowledge and skills will be carried out with education and training (training) and workshops, as well as the addition of instruments to increase women's participation in village governance. At the end of the training implementation, the community was given a response as evaluation material, and documentation of increasing women's participation in village governance. Furthermore, in the final stage of the activity, namely the closing and evaluation stage, in which a thorough assessment of the implementation of the activity